Lighting for the human circadian clock: recent research indicates that lighting has become a public health issue - Pauley, Stephen M. (Medical hypotheses, 2004)
The hypothesis that the suppression of melatonin (MLT) by exposure to light at night (LAN) may be one reason for the higher rates of breast and colorectal cancers in the developed world deserves more attention. The literature supports raising this subject for awareness as a growing public health issue. Evidence now exists that indirectly links exposures to LAN to human breast and colorectal cancers in shift workers. The hypothesis begs an even larger question: has medical science overlooked the suppression of MLT by LAN as a contributor to the overall incidence of cancer? The indirect linkage of breast cancer to LAN is further supported by laboratory rat experiments by David E. Blask and colleagues. Experiments involved the implanting of human MCF-7 breast cancer cell xenografts into the groins of rats and measurements were made of cancer cell growth rates, the uptake of linoleic acid (LA), and MLT levels. One group of implanted rats were placed in light–dark (12L:12D) and a second group in light–light (12L:12L) environments. Constant light suppressed MLT, increased cancer cell growth rates, and increased LA uptake into cancer cells. The opposite was seen in the light–dark group. The proposed mechanism is the suppression of nocturnal MLT by exposure to LAN and subsequent lack of protection by MLT on cancer cell receptor sites which allows the uptake of LA which in turn enhances the growth of cancer cells. MLT is a protective, oncostatic hormone and strong antioxidant having evolved in all plants and animals over the millennia. In vertebrates, MLT is normally produced by the pineal gland during the early morning hours of darkness, even in nocturnal animals, and is suppressed by exposure to LAN. Daily entrainment of the human circadian clock is important for good human health. These studies suggest that the proper use and color of indoor and outdoor lighting is important to the health of both humans and ecosystems. Lighting fixtures should be designed to minimize interference with normal circadian rhythms in plants and animals. New discoveries on blue-light-sensitive retinal ganglion cell light receptors that control the circadian clock and how those receptors relate to today's modern high intensity discharge (HID) lamps are discussed. There is a brief discussion of circadian rhythms and light pollution. With the precautionary principle in mind, practical suggestions are offered for better indoor and outdoor lighting practices designed to safeguard human health.